2019
DOI: 10.3389/fevo.2019.00237
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Dynamics of Natural and Restored Bolboschoenus maritimus Saltmarsh

Abstract: Saltmarshes are biogeomorphic ecosystems comprising halophytic plant communities typically located on low energy temperate coasts. Their distribution and structure are controlled by several key drivers, including sediment supply, type of vegetation, elevation, and local hydrodynamics. These dynamic systems are highly vulnerable and estimated to be experiencing annual losses of 1-2% globally. Past restoration efforts have largely implemented managed realignment strategies, however, examples of, and research on,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The studies following the first focus identified mismatches in traits that would otherwise be expected to be correlated, for example, a mismatch between the abundance and recruitment rate of mussel larvae [20]. The other studies [59,60] compared the provision of ecosystem services or function of natural and restored ecosystems formulating this comparison as a question of (mis)match.…”
Section: Functional-conceptual Mismatchesmentioning
confidence: 99%
“…The studies following the first focus identified mismatches in traits that would otherwise be expected to be correlated, for example, a mismatch between the abundance and recruitment rate of mussel larvae [20]. The other studies [59,60] compared the provision of ecosystem services or function of natural and restored ecosystems formulating this comparison as a question of (mis)match.…”
Section: Functional-conceptual Mismatchesmentioning
confidence: 99%
“…It is widely recognised that the organisation of plants and their communities often affects the occurrence of geomorphological processes (García-Ruiz, 2015). How vegetation influences sediment dynamics, including sediment settlement, deposition, and accretion rates, was studied by Taylor et al (2019) for restoration purposes. In Gallocanta Lake, the sandy barriers are considered to be one of the main geomorphodynamic units in spite of their limited surface area (less than 2% of the studied area).…”
Section: Vegetation Conditions the Local Genesis Of Landformsmentioning
confidence: 99%
“…Additionally, many of these areas suffer mounting touristic pressure, further contributing to their deterioration [ 3 ]. Today, many protection measures are in place to safeguard the remaining littoral salt marshes from human activity and the threat posed by the predicted rise in sea level as a consequence of climate change [ 4 , 5 ]. Indeed, nowadays, it is widely recognised that salt marshes perform highly valuable ecosystem services in coastal defence and wildlife conservation [ 6 , 7 ], providing a habitat for migratory waterfowl, transient marine species, and indigenous flora and fauna.…”
Section: Introductionmentioning
confidence: 99%